System upgrade for μBq/m3 level 222Rn concentration measurement. (8th March 2023) - Liu, Y.; Zhang, Y.P.; Liu, J.C.; Guo, C.; Yang, C.G.; Zhang, P.; Tang, Q.; Xu, Z.F.; Li, C.; Guan, T.Y.; Wang, S.B.
Abstract: The Jiangmen Underground Neutrino Observatory (JUNO), a 20 kton multipurpose underground liquid scintillator detector, was proposed for the determination of the neutrino mass hierarchy as primary physics goal. The central detector will be submerged in a water Cherenkov detector to lower the background from the environment and cosmic muons. Radon is one of the primary background sources. Nitrogen will be used in several sub-systems, and a highly sensitive radon detector has to be developed to measure its radon concentration. A system has been developed based on 222 Rn enrichment of activated carbon and 222 Rn detection based on the electrostatic collection. This paper presents the detail of a μBq/m 3 level 222 Rn concentration measurement system and gives detailed information about how the adsorption coefficient was measured and how the temperature, flow rate, and 222 Rn concentration affect the adsorption coefficient.